2003
DOI: 10.1160/th03-02-0102
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor cell-induced platelet aggregation and lung metastasis by the oral GpIIb/IIIa antagonist XV454

Abstract: Platelets are known to play a role in blood borne metastasis. Previous experimental studies have suggested that platelet GpIIb/IIIa may be a therapeutic target. However, the need for intravenous administration limits the potential application of current GpIIb/IIIa inhibitors to cancer therapy. The aim of the present study was to assess the efficacy of a novel, non-peptide oral GpIIb/IIIa antagonist (XV454) on tumor cell-induced platelet aggregation in vivo and on experimental metastasis. A Lewis lung carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…Abciximab) reduced tumor cell induced platelet aggregations and demonstrated antineoplastic effects [86]. Similarly, small molecule oral antagonist of GPIIb/IIIa was shown to efficiently reduce platelet aggregation and metastasis [87].…”
Section: Platelets As Therapeutic Targets For Anti-cancer Therapiesmentioning
confidence: 99%
“…Abciximab) reduced tumor cell induced platelet aggregations and demonstrated antineoplastic effects [86]. Similarly, small molecule oral antagonist of GPIIb/IIIa was shown to efficiently reduce platelet aggregation and metastasis [87].…”
Section: Platelets As Therapeutic Targets For Anti-cancer Therapiesmentioning
confidence: 99%
“…Accumulating evidence indicates that blocking the function of platelet integrin a IIb b 3 with antagonists can effectively inhibit the initial formation of tumor cell-platelet complexes and prevent hematogenous metastasis, and competitive inhibition of integrin a IIb b 3 , or treatment of a IIb or b 3 subunit with antibodies also diminish metastatic potential. [9][10][11] Some drugs with anticoagulant activities, such as aspirin, hirudin and heparin have been demonstrated to prevent tumor metastasis by the mechanisms of inhibiting tumor cell-induced platelet aggregation. 3,12,13 Heparin is most well known for its anticoagulant activity.…”
Section: Uiccmentioning
confidence: 99%
“…Since 1968, when Gasic et al (3) showed that experimental pulmonary metastasis is reduced by platelet depletion and restored by supplementation of platelets, there has been much research supporting the concept of enhancement of cancer metastasis by platelets (4). Inhibition of platelet function using integrin subunit ā£ IIb inhibitors or to a lesser effect using aspirin also inhibits metastasis (5,6). Platelet depletion or anticoagulation only has an inhibitory effect during a short time (0 -6 hours) after introduction of the tumor cells into the circulation.…”
Section: Introductionmentioning
confidence: 99%